Reaction to diseases and yield of eleven cultivars of sour-passion fruit cultivated with no pesticides - Junqueira, Nilton Tadeu Vilela; Anjos, José Ribamar Nazareno dos; Silva, Ana Paula de Oliveira; Chaves, Renata da Costa; Gomes, Antônio Carlos (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to evaluate the reaction to diseases and the yield of eleven sour-passion fruit cultivars during the first six months of harvesting in the Federal District, Brazil. Weeds were controlled using a polyethylene black cloth (mulching) with 1.20 m large on the tape of dripping irrigation along the planting line. The hybrid EC-RFM (Passiflora edulis f. flavicarpa x P. edulis) had the best yield and it was less susceptible to woodiness virus (PWV), fruit-anthracnose and septoriose. All cultivars were susceptible to fruit-scab and bacterial spot. All cultivars evaluated presented low genetic variability to disease resistance.